TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA MENURUT SISTEM PERADILAN PIDANA DALAM PERSPEKTIF RESTORATIVE JUSTICE - Mansyur, Ridwan (Jurnal Hukum dan Peradilan, 2016)
There are many domestic violence settlement that do not satisfy the sense of justice, especially for the victims and subordinate in the household. The dissertation results: first, the settlement of domestic violence in fact settled by Act No. 23 of 2004 as lex specialis. The setlements of domestic violence cases based on that rule, empirically emphasis on the criminal sanction, so that the purpose of preventive, protective and consolidative was not rise. Second, the research concluded that domestic violence is a case with multi-dimensional settlement because there is the scope of the civil and criminal sphere on the other side. Therefore, it needs a medium in the system that can accommodate the completion of the case, which one of them is restorative justice approach.Keywords: crime, domestic violence, criminal justice system, restorative justice